Natural resource management in the hillsides of Honduras: bioeconomic modeling at the micro-watershed level - Barbier, Bruno; Bergeron, Gilles (International Food Policy Research Institute, 1998)
The objective of this study is to simulate the effect of population pressure, market integration, technological improvement and policy decisions on natural resource management in the hillsides of Honduras. To do so, we developed a bioeconomic model that combines dynamic linear programming with a biophysical model, then applied this model to a typical microwatershed. Over recent years, farmers from the selected microwatershed have followed a vegetables-intensive pathway of development. We ran different scenarios with historical data over the period 1975 to 1995 and then projected 25 years into the future from 1995 to 2020. The results of the bioeconomic model presented in this paper help to test a number of induced innovation hypotheses. Many of our hypotheses are confirmed, but some of the model's results challenge conventional wisdom. The simulation results confirm that technology improvements such as irrigation and new varieties can help overcome diminishing returns to labor due to population pressure.